Study of the Influence of Surface Roughness of Carbon Fiber Reinforced Plastics on the Sealability of Disconnectable Joints in Rocket and Space Technology - Litot, Oleksandr; Manko, Tamara (Challenges and Issues of Modern Science, 2023)
In rocket and space technology, there are increased requirements for the strength and reliability of structures under operating conditions. The use of composite materials, especially carbon fiber reinforced plastics, is justified by their high specific strength and reliability both as components and as part of the reinforced material, for complex and aggressive environments such as working gases and liquids at temperatures from minus 196ºC to plus 100 ºC. Considering that a significant part of the dry weight of the launch vehicle consists of components such as fuel tanks and cryogenic pipelines, the task of reducing the weight of the upper stages of the launch vehicle, as well as the entire light class, where efficient all-composite linerless structures of cryogenic fuel tanks and pipelines can be realized, is particularly critical. This leads to the need to perform detachable flanged connections at the junction of tank-pipeline components and to ensure their tightness under operating conditions. The design task is particularly complicated when modeling the interaction of all structural elements under load conditions and cryogenic temperatures. This includes maintaining the strength and sufficient rigidity of the material and structural elements under prolonged external factors. The tightness of the detachable flanged connection is significantly affected by the difference in the coefficients of linear thermal expansion of the materials and components in contact, which, when using carbon fiber reinforced plastics, depends significantly on the reinforcement scheme of the component. The paper discusses the issue of ensuring the tightness of the flanged detachable connection made of carbon fiber reinforced plastic for cryogenic fuel components.